“Criteria for establishing a model for defining Croatian regions lagging in Development” - Krešimir Jurlin; Sanja Maleković; Jakša Puljiz (European Regional Science Association (ERSA), 2001)
Krešimir Jurlin, Jakša Puljiz, Sanja Malekoviæ Institute for International Relations, Zagreb The purpose of this paper is to introduce economic and demographic development criteria as a basis for Croatia's regional policy. The paper is the result of a project whose main objective was to provide an analytical basis for developing a model for defining the level of development of the Croatian territorial units, with the aim of widening the span of territorial units which are currrently receiving government support under the “Law on areas of specific government's concern”. The result of this project was a list of the least developed areas in Croatia, as well as a model for evaluating their development. The contents of the paper are basically the following: the criteria on the basis of which the evluation was carried out; the statistical basis and indicators of development; the creation of the development index; the evaluation model and criteria for classification; the testing of the model and experimental classification of the territorial units. Proposal: To be included under theme 1: Regional science
Keywords: 330